Determining critical power and W' in running: Accuracy of different two-point models using the power metric - Ruiz-Alias, S. A.; Ñancupil-Andrade, A. A.; Pérez-Castilla, A.; García-Pinillos, F. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study aims to determine the validity of the critical power (CP) and the work capacity over CP (W') obtained from different two-time trial combinations with respect a five-point model. In a 3-week training period, 15 athletes (age: 23 ± 5 years; height: 166 ± 6 cm; body mass: 58 ± 8 kg; 5 km season-best: 15:29 ± 00:53 mm:ss) performed five time-trials (i.e. 3, 4, 5, 10, 20 min) on a 400 m track, from which the mean power outputs were obtained through the Stryd Power Meter. An acceptable level of agreement was considered if the following criteria were met: low bias and standard error of the estimate (SEE) (<14 W [values corresponding to the ±5% of the mean CP]; W': <2.0 kJ [values corresponding to the ±10% of the mean W']), R2 > 0.90, and ICC > 0.81. The CP presented an acceptable SEE for CPwork (1.3 ± 0.5%) and CP1/time (2.7 ± 1.1%) when using the five time-trials. For both CP models, the 3-10 min was the shortest valid combination, whereas the 3-20, 4-20, and 5-20 min showed the greatest level of agreement. The W' presented a high SEE for CPwork (14.1 ± 5.2%) and CP1/time (13.8 ± 6.2%) when using the five time-trials, therefore, none of the two time-trials combinations were considered. The CP parameter can be accurately estimated from different two time-trial combinations, whereas none reached an acceptable level of accuracy for the determination of W'.